Logico Semantic Relation In an Article "Motivation in Education" by Diana Stirling - Daullah Nurkaromah (PROJECT (Professional Journal of English Education), 2019)
AbstractThis research focused on the analysis of conjuction in articles entitled "motivation in education" by Diana Stirling. The conjunction has an important function for a text because it connects one unit and another unit to make text. Informing cohesive sentences that require proper conjunction to make easier for a readers to understand the contents of the text. Conjunction consists of three parts, namely of elaboration, extention, and enhancement. In this research, the researcher analyzed an article titled "motivation in education" by Diana Stirling regarding the use of deep conjunctions of the article and how many conjunctions are used in article. The method used  is qualitative to analyze conjunction in a article. The result showed that from this research Diana Stirling gave many addition to support her argument and present them the fact. The total of addition is 75 from 96 conjunctions. Keywords:  Conjunction, Elaboration, Extention, Enhancement